Linguistic spin in randomized controlled trials about age-related macular degeneration - Veldhuis, Nienke; Nuijts, Myrthe A.; Isphording, Luka; Lee-Kong, Felicia V. Y. L.; Imhof, Saskia M.; Stegeman, Inge (Frontiers in Epidemiology, 2022)
Objective To evaluate the prevalence, type and extent of linguistic spin in randomized controlled trials (RCTs) exploring interventions in patients with age-related macular degeneration (AMD), as well as to investigate whether study variables were correlated with linguistic spin. Study design and setting PubMed was searched from 2011 to 2020 to identify RCTs including patients with AMD. Two authors independently assessed a total of 96 RCTs. Linear regression analyses were performed to investigate whether linguistic spin was correlated with predefined study variables. Results Linguistic spin was found in 61 of 96 abstracts (63.5%) and in 90 of 96 main texts (93.8%). Use of words pointing out the beneficial effect of a treatment and the use of ‘(statistically) significant/significance' without reporting a P-value or a 95% confidence interval (CI) were the most frequently identified categories of linguistic spin. Sample size was significantly correlated with the total linguistic spin score (95% CI 0.38–5.23, P = 0.02). Conclusion A high prevalence and extent of linguistic spin in RCTs about AMD was found. We highlighted the importance of objective reporting and awareness of linguistic spin among ophthalmologists and other readers.